Intra industry trade expansion and productivity growth - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2008)
We use the concept of marginal intra-industry trade (MIIT) to analyse the effect of trade expansion on labour productivity growth across 23 EU countries and 94 manufacturing sectors in 1995-2005. The highest MIIT index values are found in sectors producing differentiated goods as well as in science and scale-intensive sectors, while the lowest are found in resource and labour-intensive sectors. Thus specialisation in sectors characterised by tradi-tional comparative advantage has been associated with slower productivity growth. The results indicate that a trade-flow expansion characterised by intra-industry trade (high MIIT) is associated with faster productivity growth also after we control for the size in trade flow changes. Especially the increase in imports seems important. The analysis is mostly done using random-effects linear model specifications but further evidence is presented using several other estimation methods.
Keywords: J24; F1; C23; 330; productivity; growth; marginal intra-industry trade; Intraindustrieller Handel; Arbeitsproduktivität; Wirtschaftswachstum; Verarbeitendes Gewerbe; EU-Staaten